Portrait of members in the Izlet Bracko Drustav - Johnson, Charles Ellis (photographer):::Creator::::::::::::
Group portrait of men standing in front of trees, possibly in a park. A man at the center holds up a sign with a European flag (possibly Croatian ) crossed with an American flag that reads "1923 1925 'Bracko Drustvo' Hollister San Jose California." The men could be of Croatian decent and possibly a veterans group.